The Impact of Solid Waste on Tourism in the Doukan District Center (Raparin Journal of Humanities (RJH), 2025)
Urban solid waste is currently of great importance to the management of population areas (cities, towns, villages, temporary and seasonal settlements) in the world is constantly emphasized, the impact of this waste is clear on the tourism sector Isn't it reducing tourists? The aim of this research is to know the current management (collection, transportation and treatment) of waste in Dukan district and analyze the impact of this management (collection, transportation and treatment) on tourism in tourist attractions Administratively, it consists of six districts (Center, Khdran, Surdash, Khalkan, Piramagrun, Bangird). The method used in this study is descriptive analysis. The population of the district is constantly increasing Population activities include tourism, administrative activities, wholesale and retail trade and industrial services, small industries, two medium and one large food industries. Waste generally consists of: organic waste (food), plastic waste, glass waste, paper and cardboard waste. The Environmental Department of Dukan District Municipality is responsible for supervising this work. The work is contracted to Anzo Construction Company. It collects waste daily (except Fridays) from all sectors The total number of equipment used for collection and burial is 31. The amount of waste in the district is increasing. There is no separation of waste into sectors in this district (only waste). Their doctors have special furnaces inside the hospitals and they burn the necessary amount of medical waste. The average daily collection of waste is 79.272 tons/day, which is 1.147 kg per person Waste, obviously remaining in one place and not collecting solid waste pollutes the environment, causes air pollution and visual pollution, on the other hand spreads an unpleasant smell in the place If the company does not know, the company has set up mobile numbers for the employees and the administration of the tourist areas to call them and go directly to collect the waste. These are all reasons for the tourist areas to remain clean Travel Choose this area, the negative impact of waste transportation on the tourism sector is observed, because capsule vehicles are used to collect and transport waste, directly cover the waste and suppress the smell (to a large extent). The reason for the spread of smell and spillage of water on the streets (the administration of tourist areas have been notified in this case, I will work to minimize the mixing of water with waste). The only solution is to bury the waste underground in an area very close to the tourist center of the district, on the one hand creates problems for the soil and water of the area In the past, this has happened only once. Municipal inspectors continuously monitor (collection, transportation and treatment of waste) according to municipal guidelines. Any violation of improper collection or transportation or treatment according to guidelines It is close to 3 million Iraqi dinars, which is no less than 2 million in total and much more than the previous company.